The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.otsr.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial pullout repair of the lateral meniscus posterior root tear combined with anterior cruciate ligament reconstruction reduces lateral meniscus extrusion: A retrospective study

Abstract: Background: Lateral meniscus (LM) posterior root tears (PRT) are often associated with anterior cruciate ligament (ACL) injury and can result in rotational instability, joint overloading, and degenerative changes in the knee. Improved rotational stability and kinematics have been reported after LMPRT repair. However, it is unclear which repair technique can achieve the greatest reduction in lateral meniscus extrusion (LME).Hypothesis: We hypothesized that transtibial pullout repair would decrease LME to a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 27 publications
(34 reference statements)
0
59
0
Order By: Relevance
“…2,3,10,13,20,27,30 A critical issue for successful repair of tears of the LMPR is proper surgical technique, and meniscal extrusion is a common and objective outcome to measure postsurgical meniscal function. 1,15,18 Currently, there are 2 surgical techniques with clinical follow-up records. The side-toside technique can be used to repair radial tears with a root remnant of adequate tissue quality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,3,10,13,20,27,30 A critical issue for successful repair of tears of the LMPR is proper surgical technique, and meniscal extrusion is a common and objective outcome to measure postsurgical meniscal function. 1,15,18 Currently, there are 2 surgical techniques with clinical follow-up records. The side-toside technique can be used to repair radial tears with a root remnant of adequate tissue quality.…”
Section: Discussionmentioning
confidence: 99%
“…2,18,30 There were no significant reductions of coronal extrusion after LMPR repairs in all 3 studies, but 1 comparative study among them showed significantly greater decreases of coronal extrusion after pullout repairs than after side-to-side repairs. 18 In 2 studies repairing radial tears of the LMPR by the side-to-side suture technique, the sagittal extrusion increased in 1 study but decreased in the other. 2,30 The LMPR signal on follow-up MRI was reported in 2 studies.…”
Section: Radiographic Outcomesmentioning
confidence: 91%
See 3 more Smart Citations